A 900 MHz SAW Microstrip Antenna-Duplexer for Mobile Radio - Anemogiannis, Kimon; Beck, Christian; Roth, Alexander; Russer, Peter; Weigel, Robert (IEEE MTT-S International Microwave Symposium Digest, 1990, 1990)
A novel, 900-MHz SAW (surface acoustic wave) microstrip antenna-duplexer designed for use in European mobile radio systems is presented. The duplexer consists of a transmitter SAW filter, two receiver SAW filters, a low-noise receiver amplifier, and a duplexing microstrip circuit. A dual-track filter design using interdigital transducers for track coupling provides low insertion loss (5 dB), small passband ripple (+or-0.5 dB), high stopband rejection (50 dB), and small chip-size (TO-39 package). The filters were fabricated on 36 degrees -rotated YX-LiTaO/sub 3/ substrates with a photolithographic technique. Due to the design of the microstrip duplexer, the selectivity of the front end is enhanced by 15 dB.<>
93781a41-0f22-4bbe-83c8-b30fb0ad65d3::1512001600,anemogiannis1990
Keywords: microstrip antennas; mobile radio systems; high stopband rejection; interdigital transducers; Low-noise amplifiers; Microstrip antennas; Microstrip filters; Mobile antennas